2021
DOI: 10.1038/s41598-021-81250-3
|View full text |Cite|
|
Sign up to set email alerts
|

Functional expression of the transient receptor potential ankyrin type 1 channel in pancreatic adenocarcinoma cells

Abstract: The transient receptor potential ankyrin type 1 (TRPA1) channel belongs to the TRP superfamily of ion channels. TRPA1 is a membrane protein with multiple functions able to respond to noxious stimuli, reactive oxygen species, inflammatory cytokines or pungent substances, and it participates in pain signalling, taste, inflammation and various steps of the tumorigenic process. To date, no reports have addressed the expression and function of TRPA1 in pancreatic ductal adenocarcinoma (PDAC) cells. This work report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…3b, c and e, f). One recent study reported the endogenous expression of TRPA1 channels in human pancreatic adenocarcinoma cell lines and siRNA-induced downregulation of TRPA1 can enhance cell migration and change the cell cycle progression 18 . Moreover, emerging evidences have revealed that noncoding RNA can promote angiogenesis and metastasis through epithelial–mesenchymal transition and upregulate TRPM3 in renal cell carcinoma 19 .…”
Section: Resultsmentioning
confidence: 99%
“…3b, c and e, f). One recent study reported the endogenous expression of TRPA1 channels in human pancreatic adenocarcinoma cell lines and siRNA-induced downregulation of TRPA1 can enhance cell migration and change the cell cycle progression 18 . Moreover, emerging evidences have revealed that noncoding RNA can promote angiogenesis and metastasis through epithelial–mesenchymal transition and upregulate TRPM3 in renal cell carcinoma 19 .…”
Section: Resultsmentioning
confidence: 99%
“…TRPA1 has been described to be upregulated in different tumors, such as nasopharyngeal carcinoma [33], pancreatic adenocarcinoma [32] and prostate cancer-associated fibroblast cell cultures [45]. Elevated TRPV1 expression was shown in breast and prostate cancer [45].…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 activation by AITC promoted the survival and proliferation of human small cell lung cancer cell line [13]. It was shown that TRPA1 inhibits Panc-1 pancreatic ductal adenocarcinoma cell line cells migration both via channel dependent and independent pathways [32]. TRPA1 upregulation was detected by immunohistochemistry in nasopharyngeal carcinoma patients, which was negatively predictive for disease-specific, distal metastasis-and local recurrence-free survivals [33,34].…”
Section: Introductionmentioning
confidence: 97%
“…In many cancers, including PDAC, TRPA1 stimulates tolerance to oxidative stress [ 9 ]. In our previous studies, we reported the expression of functional TRPA1 channels in PDAC cell lines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a quest to complete our previous studies and previous reports regarding TRP channels in PDAC cell lines [ 7 , 8 , 10 , 13 , 14 ], in this study, we aimed to determine the expression levels of three TRP channels ( TRPM8 , TRPA1 , and TRPV6 ) and associated factors TCAF1 ( FAM115A ) and TCAF2 ( FAM115C ) in the tumoral tissues of PDAC patients, and to correlate them with pathophysiological data. For this purpose, we used public databases and web-based tools for the analysis of RNA-sequencing data, as well as a validation cohort including PDAC patients from the Fundeni Clinical Institute.…”
Section: Introductionmentioning
confidence: 99%